Electromyographic response of vastus lateralis, vastus medialis and rectus femoris muscles during anaerobic intermittent effort in cyclists - Okano, Alexandre Hideki (2007)
The purpose of the present study was to investigate the neuromuscular recruitment characteristics of vastus lateralis (VL), vastus medialis (VM), and rectus femoris (RF) during anaerobic intermittent effort in cyclists and the relationships between electromyographic signal of muscles and physical performance. Nine males cyclists (age 18-30 years) performed three Wingate Test (W1, W2, and W3) on a cycle ergometer with two minutes of rest between each exercise bout. Relative mean power (RMP), root mean square amplitude (EMG-RMS), and median frequency (Fourier Transform) were recorded throughout the cycling. RMP decreased significantly between W1 and W3 by 27%. EMG-RMS decrease was slightly more pronounced for RF (13%) than VL and VM (6%). The different EMG-RMS fatigue patterns between the VL, VM, and RF may be explained by morphological, architecture, and biomechanical factors. We concluded that EMG-RMS fatigue patterns were different between the VL, VM, and RF. MPO and EMG-RMS declined during high intensity exercise but not in the same proportion. Further investigation is required to measure both metabolite accumulation and changes in neural firing patterns during high intensity intermittent effort.